Writing after betrayal: Desahogarse, street outreach, and ethnography. (September 2019) - Wolseth, Jon
Ethnographers may experience troubling relationships while conducting research. Strained interpersonal relationships with members of the communities where ethnographers work can be caused by emotional entanglements, acts of violence, or betrayal. When harm occurs, ethnographers are faced with ethical and emotional challenges about reporting one's experience versus descriptions of social facts. This article compares desahogarse, a way of speaking on Dominican streets used to express everyday betrayals, with the genre of the narrative ethnography to explore modes of presenting the contextualized self in fieldwork. In particular, the use of the textual strategies of perspective and composite characters and events are explored as writing approaches when faced with a troubled fieldwork relationship that had ethical implications on the access to the street community being researched. Ethnographers should consider the ethical, representational, and analytical gains of an ethnography that relies on a deliberate, if partial, exploration of the emotional experiences of fieldwork.